Method for preparing high-capacity electrode material based on zinc smelting anode slime, electrode material and application
Through wet leaching and vulcanization baking technology, the problem of high added value utilization of zinc smelting anode sludge is solved, and the preparation of high capacity and high active electrode materials and the excellent performance of lithium-ion batteries are achieved.
Patent Information
- Application Number
- CN202411673941.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-28
AI Technical Summary
The high added value utilization level of zinc smelting anode mud is low, resulting in waste of resources and a great impact on the environment, making it difficult to achieve high-quality utilization of solid waste resources.
Useful transition metal elements such as manganese, zinc and lead are selectively extracted from zinc smelting anode sludge through wet leaching technology, and converted into mixed transition metal sulfides through hydrolyzed precipitation and sulfide roasting, which are used to prepare high-capacity and highly active electrode materials.
The high-quality utilization of zinc smelting anode mud has been achieved, the recycling rate of transition metal elements has been improved, the preparation process of electrode materials has been shortened, the production cost has been reduced, and the advantages of high activity and high capacity have been shown in lithium-ion batteries.
Smart Images

Figure CN119528205A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrode material, in particular to a high-capacity electrode material, and also to a method for preparing the high-capacity electrode material based on zinc smelting anode mud, and application of the high-capacity electrode material in a lithium-ion battery, belonging to the technical field of high-value resource utilization of solid waste. Background Art
[0002] During the zinc electrolysis process, the zinc in the anode will dissolve and transfer to the cathode, while other metals or elements that do not participate in the electrolysis reaction will remain on the anode in the form of a single substance, alloy or compound, eventually forming anode mud. These elements include but are not limited to manganese, lead, silver, etc., which cannot be completely dissolved in the electrolyte due to their electrochemical properties, thus forming anode mud; based on this, the main component of zinc smelting anode mud is manganese dioxide, and it also contains lead compounds, zinc sulfate and other substances. For many years, the disposal method of zinc smelting anode mud has mostly been to treat the smelting mud in a lead-zinc smelter. This treatment method has a great impact on the environment and the economic added value of recycling, and it is difficult to achieve high-quality utilization of solid waste resources, resulting in serious waste of resources. Therefore, it is urgent to find a method that can increase the added value of transition metal elements in zinc smelting anode mud. Summary of the invention
[0003] In view of the problems of low level of high added value utilization of zinc smelting anode mud in the prior art, the first object of the present invention is to provide a method for preparing high-capacity electrode material based on zinc smelting anode mud, which can realize the resource utilization of zinc smelting anode mud, selectively leach useful transition metals such as manganese, zinc and lead in zinc smelting anode mud and convert them into mixed transition metal sulfides, which can be used as high-capacity and high-activity electrode materials, thereby realizing high-quality utilization of zinc smelting anode mud. The method is simple, high-quality, economically valuable and widely applicable.
[0004] The second object of the present invention is to provide a high-capacity electrode material, which is composed of mixed transition metal sulfides such as manganese, lead, and zinc, and has the characteristics of high capacity and high activity.
[0005] The third object of the present invention is to provide an application of a high-capacity electrode material, which is used as a negative electrode material in lithium-ion batteries and exhibits advantages such as high activity and high capacity.
[0006] In order to achieve the above technical objectives, the present invention provides a method for preparing a high-capacity electrode material based on zinc smelting anode mud, the method comprising: subjecting zinc smelting anode mud to wet leaching to obtain a mixed transition metal ion solution; the mixed transition metal ion solution is subjected to hydrolysis and precipitation to obtain a transition metal mixed gel; the transition metal mixed gel is subjected to sulfurization and roasting to obtain an electrode material; the wet leaching adopts at least one of an acid solution containing ferrous ions, an acid solution containing hydrogen peroxide, and an acid solution containing sulfite as a leaching agent.
[0007] The method for preparing high-capacity electrode materials based on zinc smelting anode mud provided by the present invention can realize the recovery and high-value utilization of useful transition metal ions in zinc smelting anode mud. The key to the technical solution of the present invention is to first realize the selective leaching of useful transition metal elements in zinc smelting anode mud by wet leaching (mainly leaching transition metal elements such as manganese, zinc and lead), and the leached useful transition metal elements do not need purification and impurity removal processes, and are directly converted into mixed transition metal sulfides through hydrolysis precipitation and sulfidation roasting, especially the mixed transition metal ions are precipitated in the form of eutectic, and nano-precipitation is formed, which realizes the uniform doping and co-sulfurization of mixed transition metal ions, and the formed mixed transition metal sulfides show the characteristics of high capacity and high activity. The present invention innovatively directly and selectively extracts useful transition metal elements from zinc smelting anode mud and converts them into high-activity and high-capacity electrode materials, which can not only complete the high-quality utilization of zinc smelting anode mud, but also shorten the preparation process of electrode materials and significantly reduce the production cost of electrode materials.
[0008] As a preferred solution, the concentration of ferrous ions in the acid solution containing ferrous ions is 0.05 to 0.5 mol L -1 The acid concentration is 0.5 to 2 mol L -1 As a preferred solution, the concentration of hydrogen peroxide in the acid solution containing hydrogen peroxide is 0.05 to 0.5 mol L -1 The acid concentration is 0.5 to 2 mol L -1 As a preferred embodiment, the concentration of sulfite in the sulfite-containing acid solution is 0.05 to 0.5 mol L -1 The acid concentration is 0.5 to 2 mol L -1 The sulfite may be ammonium sulfite. The ferrous ions in the acid solution containing ferrous ions are provided by soluble salts such as ferrous chloride and ferrous sulfate, and the acid component in the acid solution may be provided by conventional inorganic acids, such as sulfuric acid and hydrochloric acid. The present invention can achieve reduction leaching of high-valent manganese by adopting a reduction leaching method, reduce the valence state of manganese elements, and accelerate the dissolution of manganese elements, for example: 2Fe 2+ +MnO2+4H + →2Fe 3+ +Mn2+ +4H2O, the acidic solution can provide abundant hydrogen ions to help reduce the oxygen produced by leaching to form water, causing the reaction to move to the right and improve the leaching efficiency of manganese.
[0009] As a preferred solution, the conditions for wet leaching are: liquid-solid ratio of 1mL:1g~100mL:1g, leaching temperature of 30℃~100℃, and leaching time of 0.5h~12h. If the liquid-solid ratio of wet leaching is too low, it will make it difficult for zinc smelting materials to be effectively dispersed in the leaching solution, resulting in transition metal elements such as manganese and zinc being unable to be efficiently extracted. If the liquid-solid ratio is too large, it will cause a large amount of waste liquid to be generated, pollute the environment, and increase subsequent processing costs. Therefore, the liquid-solid ratio is further preferably 5mL:1g~50mL:1g. The increase in temperature and the improvement of leaching time help to increase the probability of collision between reducing ions, acidic protons, etc. and manganese dioxide, accelerate the progress of the reaction, improve the leaching efficiency, and realize the rapid leaching of manganese ions, but it is possible to cause the reduction leaching of other high-priced impurity elements, resulting in an increase in the impurity content inside the material, and the derived high-capacity new materials have too many impurity components, resulting in poor electrochemical performance. The leaching time is too short and the temperature is too low, which causes a serious decline in the manganese leaching efficiency, increased energy consumption and cost, and is not conducive to expanding production.
[0010] As a preferred embodiment, the hydrolysis precipitate is prepared at a concentration of 0.1 mol L -1 ~2.0mol L -1 The alkaline solution is used as a precipitant; the alkaline solution includes at least one of sodium hydroxide solution, lithium hydroxide solution, potassium hydroxide solution, and ammonia water. If the concentration of the precipitant is too low, it is difficult to completely precipitate the useful transition metal elements. If the concentration of the alkaline solution is too high, it will not only cause a waste of the alkaline solution, but also cause the precipitation rate of the useful transition metal elements to be too fast due to the high alkalinity, making it difficult for the transition metal mixed gel to achieve nano-size and produce obvious agglomeration, resulting in poor subsequent sulfurization activation effect.
[0011] As a preferred solution, thiourea and / or sulfur powder are used as vulcanizing agents during the sulfurization and roasting process.
[0012] As a preferred solution, the mass of the vulcanizing agent is 2 to 10 times the mass of the transition metal mixed gel. The mass of the vulcanizing agent is further preferably 2 to 5 times the mass of the transition metal mixed gel; when the amount of sulfur source added is too much, part of the sulfur resources will be volatilized and wasted, and it is also possible that part of the sulfur element remains in the electrode material, resulting in poor electrochemical performance of the regenerated material; when the amount of sulfur source added is too low, part of the transition metal will not be vulcanized, which will affect the electrochemical performance of the electrode material.
[0013] As a preferred solution, the calcination conditions are: in a protective atmosphere, at 5 to 15 ° C min -1 The heating rate is raised to 500-800°C, and the calcination is carried out for 4h-10h. The protective atmosphere is argon, nitrogen or hydrogen-argon mixed gas (the volume ratio of hydrogen is 5%-30%). Preferably, the hydrogen-argon mixed gas (the volume ratio of hydrogen is 5%-30%). Based on the fact that the transition metal mixed gel contains a large amount of water and hydroxide, if it is calcined in the air, the sulfur source has no time to react with the metal hydroxide gel, and it will first react with the oxygen component in the air, resulting in the final metal hydroxide being difficult to completely sulfide; adding a reducing atmosphere to the inert atmosphere, the sulfur source will first form hydrogen sulfide gas, and with the help of acidic protons, it will first react with the hydroxide in the metal hydroxide gel, and the sulfur element will quickly react with the metal ions to form metal sulfides. If the sulfurization roasting temperature is too low, the sulfurization effect cannot be achieved. If the sulfurization roasting temperature is too high, part of the sulfur will be volatilized and lost, resulting in part of the transition metal being difficult to fully sulfide. A further preferred Fuan Shao temperature is 500-700°C.
[0014] The invention also provides a high-capacity electrode material, which is obtained by the preparation method.
[0015] The present invention also provides an application of the high-capacity electrode material, which is used as a negative electrode material in a lithium-ion battery.
[0016] The zinc smelting anode mud of the present invention mainly comes from the anode mud material purchased on the market. The main component of the zinc anode mud is manganese dioxide, and it also contains elements such as Pb, Zn, Fe, Ca, Mg, Sr and crystalline substances. Its chemical composition usually meets the requirements of Pb≤15%, Zn≤25%, MnO2>40%, silver≥0.005%, and H2O≤30%.
[0017] Compared with the prior art, the technical solution of the present invention brings the following beneficial technical effects:
[0018] The present invention selectively extracts key useful transition metal elements from zinc smelting anode mud to obtain a leaching solution with rich content of mixed transition metal elements such as manganese and zinc, and then precipitates and sulfides the transition metal elements in the leaching solution to obtain a highly active electrode material.
[0019] The present invention can realize the short-process extraction and use of key transition metal elements in zinc smelting, avoiding the large acid and alkali consumption and high energy consumption of the traditional full-element leaching method. The leachate is directly used to prepare high-capacity active materials, avoiding the secondary purification and deep processing process of the leachate, and improving the element recovery rate.
[0020] The high-capacity electrode material of the present invention is used as a negative electrode material for lithium-ion batteries, and exhibits advantages such as high activity and high capacity.
[0021] The high-capacity electrode material preparation method of the present invention has the advantages of simple operation, low energy consumption, good effect, high efficiency and easy promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 XRD of zinc smelting anode mud.
[0023] Figure 2 This is the distribution diagram of various elements in zinc smelting anode mud. DETAILED DESCRIPTION
[0024] The following examples are used to illustrate the present invention, but are not intended to limit the scope of protection of the claims of the present invention.
[0025] The zinc smelting anode mud used in the present invention is derived from the anode mud produced in the factory. Its composition is shown in Table 1. The raw material analysis is as follows: Figure 1 , 2 shown.
[0026] Table 1 Distribution of elements in zinc smelting anode mud
[0027]
[0028] Example 1
[0029] 1) Take 1g of zinc smelting anode mud, reduce its particle size by ball milling, and then disperse it in 10ml of leaching solution, which is a mixed solution of hydrogen peroxide and sulfuric acid (acid concentration is 1.0molL -1 , H2O2 concentration is 0.1 mol L -1 ), at 50°C, stirring was continued for 6h;
[0030] 2) The mixed solution was vacuum filtered to separate the leaching solution (the manganese leaching concentration was 5.2 g / L -1 , the zinc leaching concentration is 0.3gL -1 ), put 1.0 molL -1 of sodium hydroxide solution and continued stirring; performing vacuum filtration to obtain a transition metal mixed gel residue;
[0031] 3) freeze-drying the transition metal mixed gel residue, grinding it, and then mixing it with thiourea at a mixing mass ratio of 1:3, and then placing it in a tube furnace and calcining it in a hydrogen-argon mixed atmosphere (hydrogen mass ratio 5%) at a calcination temperature of 600°C and a heating rate of 8°C min -1 , the calcination time is 5h, and a high-activity and high-capacity electrode material is obtained.
[0032] Embodiment 2:
[0033] 1) Take 1g of zinc smelting anode mud, reduce its particle size by ball milling, and then disperse it in 10ml of leaching solution, the leaching solution is a mixed solution of ferrous sulfate and sulfuric acid (acid concentration is 1.0molL -1 , the concentration of ferrous sulfate is 0.1 molL -1 ), at 50°C, stirring was continued for 6h;
[0034] 2) The mixed solution was vacuum filtered to separate the leaching solution (the manganese leaching concentration was 5.4 g / L -1 The zinc leaching concentration is 0.51 g / L -1 ), put 1.0 molL -1 of sodium hydroxide solution and continued stirring; performing vacuum filtration to obtain a transition metal mixed gel residue;
[0035] 3) freeze-drying the transition metal mixed gel residue, grinding it, and then mixing it with thiourea at a mixing mass ratio of 1:3, and then placing it in a tube furnace and calcining it in a hydrogen-argon mixed atmosphere (hydrogen mass ratio 5%) at a calcination temperature of 600°C and a heating rate of 8°C min -1 , the calcination time is 5h, and a high-activity and high-capacity electrode material is obtained.
[0036] Embodiment 3:
[0037] 1) Take 1g of zinc smelting anode mud, reduce its particle size by ball milling, and then disperse it in 5mL of leaching solution, the leaching solution is a mixed solution of hydrogen peroxide and sulfuric acid (acid concentration is 1.0molL -1 , H2O2 concentration is 0.1 molL -1 ), at 50°C, stirring was continued for 6h;
[0038] 2) The mixed solution was vacuum filtered to separate the leaching solution (the manganese leaching concentration was 2.6 g / L -1 , the zinc leaching concentration is 0.1gL -1 ), put 1.0 molL -1 of sodium hydroxide solution and continued stirring; performing vacuum filtration to obtain a transition metal mixed gel residue;
[0039] 3) freeze-drying the transition metal mixed gel residue, grinding it, and then mixing it with thiourea at a mixing mass ratio of 1:3, and then placing it in a tube furnace and calcining it in a hydrogen-argon mixed atmosphere (hydrogen mass ratio 5%) at a calcination temperature of 600°C and a heating rate of 8°C min -1 , the calcination time is 5h, and a high-activity and high-capacity electrode material is obtained.
[0040] Embodiment 4:
[0041] 1) Take 1g of zinc smelting anode mud, reduce its particle size by ball milling, and then disperse it in 100mL of leaching solution, the leaching solution is a mixed solution of hydrogen peroxide and sulfuric acid (acid concentration is 1.0molL -1 , H2O2 concentration is 0.1 molL -1 ), at 50°C, stirring was continued for 6h;
[0042] 2) The mixed solution was vacuum filtered to separate the leaching solution (the manganese leaching concentration was 0.9 g / L -1 , the zinc leaching concentration is 0.02gL -1 ), put 1.0 molL -1 of sodium hydroxide solution and continued stirring; performing vacuum filtration to obtain a transition metal mixed gel residue;
[0043] 3) freeze-drying the transition metal mixed gel residue, grinding it, and then mixing it with thiourea at a mixing mass ratio of 1:3, and then placing it in a tube furnace and calcining it in a hydrogen-argon mixed atmosphere (hydrogen mass ratio 5%) at a calcination temperature of 600°C and a heating rate of 8°C min -1 , the calcination time is 5h, and a high-activity and high-capacity electrode material is obtained.
[0044] Embodiment 5:
[0045] 1) Take 1g of zinc smelting anode mud, reduce its particle size by ball milling, and then disperse it in 10mL of leaching solution, the leaching solution is a mixed solution of hydrogen peroxide and sulfuric acid (acid concentration is 1.0molL -1 , H2O2 concentration is 0.1 molL -1 ), at 30°C, stirring was continued for 6 h;
[0046] 2) The mixed solution was vacuum filtered to separate the leaching solution (the manganese leaching concentration was 4.7 g / L -1 , the zinc leaching concentration is 0.3gL -1 ), put 1.0 molL -1 of sodium hydroxide solution and continued stirring; performing vacuum filtration to obtain a transition metal mixed gel residue;
[0047] 3) freeze-drying the transition metal mixed gel residue, grinding it, and then mixing it with thiourea at a mixing mass ratio of 1:3, and then placing it in a tube furnace and calcining it in a hydrogen-argon mixed atmosphere (hydrogen mass ratio 5%) at a calcination temperature of 600°C and a heating rate of 8°C min -1 , the calcination time is 5h, and a high-activity and high-capacity electrode material is obtained.
[0048] Embodiment 6:
[0049] 1) Take 1g of zinc smelting anode mud, reduce its particle size by ball milling, and then disperse it in 10ml of leaching solution, which is a mixed solution of hydrogen peroxide and sulfuric acid (acid concentration is 1.0molL -1 , H2O2 concentration is 0.1 molL -1 ), at 100°C, stirring was continued for 6 h;
[0050] 2) The mixed solution was vacuum filtered to separate the leaching solution (the manganese leaching concentration was 6.4 g / L -1 , the zinc leaching concentration is 0.5gL -1 ), put 1.0 molL -1 of sodium hydroxide solution and continued stirring; performing vacuum filtration to obtain a transition metal mixed gel residue;
[0051] 3) freeze-drying the transition metal mixed gel residue, grinding it, and then mixing it with thiourea at a mixing mass ratio of 1:3, and then placing it in a tube furnace and calcining it in a hydrogen-argon mixed atmosphere (hydrogen mass ratio 5%) at a calcination temperature of 600°C and a heating rate of 8°C min -1 , the calcination time is 5h, and a high-activity and high-capacity electrode material is obtained.
[0052] Embodiment 7:
[0053] 1) Take 1g of zinc smelting anode mud, reduce its particle size by ball milling, and then disperse it in 10ml of leaching solution, which is a mixed solution of hydrogen peroxide and sulfuric acid (acid concentration is 1.0molL -1 , H2O2 concentration is 0.1 mol L -1 ), at 50°C, stirring continuously for 0.5h;
[0054] 2) The mixed solution was vacuum filtered to separate the leaching solution (the manganese leaching concentration was 4.8 g / L -1 , the zinc leaching concentration is 0.2gL -1 ), put 1.0 molL -1 of sodium hydroxide solution and continued stirring; performing vacuum filtration to obtain a transition metal mixed gel residue;
[0055] 3) freeze-drying the transition metal mixed gel residue, grinding it, and then mixing it with thiourea at a mixing mass ratio of 1:3, and then placing it in a tube furnace and calcining it in a hydrogen-argon mixed atmosphere (hydrogen mass ratio 5%) at a calcination temperature of 600°C and a heating rate of 8°C min -1 , the calcination time is 5h, and a high-activity and high-capacity electrode material is obtained.
[0056] Embodiment 8:
[0057] 1) Take 1g of zinc smelting anode mud, reduce its particle size by ball milling, and then disperse it in 10ml of leaching solution, the leaching solution is a mixed solution of hydrogen peroxide and sulfuric acid (acid concentration is 1.0molL -1 , H2O2 concentration is 0.1 molL -1 ), at 50°C, stirring was continued for 12h;
[0058] 2) The mixed solution was vacuum filtered to separate the leaching solution (the manganese leaching concentration was 5.9 g / L -1 , the zinc leaching concentration is 0.5gL -1 ), put 1.0 mol L -1 of sodium hydroxide solution and continued stirring; performing vacuum filtration to obtain a transition metal mixed gel residue;
[0059] 3) freeze-drying the transition metal mixed gel residue, grinding it, and then mixing it with thiourea at a mixing mass ratio of 1:3, and then placing it in a tube furnace and calcining it in a hydrogen-argon mixed atmosphere (hydrogen mass ratio 5%) at a calcination temperature of 600°C and a heating rate of 8°C min -1 , the calcination time is 5h, and a high-activity and high-capacity electrode material is obtained.
[0060] Embodiment 9:
[0061] 1) Take 1g of zinc smelting anode mud, reduce its particle size by ball milling, and then disperse it in 10ml of leaching solution, which is a mixed solution of hydrogen peroxide and sulfuric acid (acid concentration 1.0 mol L -1 , H2O2 concentration is 0.1 molL -1 ), at 50°C, stirring was continued for 6h;
[0062] 2) The mixed solution was centrifuged to separate the leaching solution (the manganese leaching concentration was 5.2 g L -1 , the zinc leaching concentration is 0.3gL -1 ), put 1.0molL -1 of sodium hydroxide solution and continued stirring; performing vacuum filtration to obtain a transition metal mixed gel residue;
[0063] 3) freeze-drying the transition metal mixed gel residue, grinding it, and then mixing it with thiourea at a mixing mass ratio of 1:3, and then placing it in a tube furnace and calcining it in a hydrogen-argon mixed atmosphere (hydrogen mass ratio 5%) at a calcination temperature of 600°C and a heating rate of 8°C min -1 , the calcination time is 5h, and a high-activity and high-capacity electrode material is obtained.
[0064] Embodiment 10:
[0065] 1) Take 1g of zinc smelting anode mud, reduce its particle size by ball milling, and then disperse it in 10mL of leaching solution, which is a mixed solution of hydrogen peroxide and sulfuric acid (acid concentration is 1.0 mol L -1 , H2O2 concentration is 0.1 molL -1 ), at 50°C, stirring was continued for 6h;
[0066] 2) The mixed solution was vacuum filtered to separate the leaching solution (the manganese leaching concentration was 5.2 g / L -1 , the zinc leaching concentration is 0.3gL -1 ), put 1.0molL -1 of potassium hydroxide solution and continued stirring; performing vacuum filtration to obtain a transition metal mixed gel residue;
[0067] 3) freeze-drying the transition metal mixed gel residue, grinding it, and then mixing it with thiourea at a mixing mass ratio of 1:3, and then placing it in a tube furnace and calcining it in a hydrogen-argon mixed atmosphere (hydrogen mass ratio 5%) at a calcination temperature of 600°C and a heating rate of 8°C min -1 , the calcination time is 5h, and a high-activity and high-capacity electrode material is obtained.
[0068] Embodiment 11:
[0069] 1) Take 1g of zinc smelting anode mud, reduce its particle size by ball milling, and then disperse it in 10ml of leaching solution, the leaching solution is a mixed solution of hydrogen peroxide and sulfuric acid (acid concentration is 1.0molL -1 , H2O2 concentration is 0.1 molL -1 ), at 50°C, stirring was continued for 6h;
[0070] 2) The mixed solution was vacuum filtered to separate the leaching solution (the leaching amount of manganese element was 5.2 g / L -1 , zinc element leaching solution concentration 0.3gL -1 ), put 0.1 mol L -1 of sodium hydroxide solution and continued stirring; performing vacuum filtration to obtain a transition metal mixed gel residue;
[0071] 3) freeze-drying the transition metal mixed gel residue, grinding it, and then mixing it with thiourea at a mixing mass ratio of 1:3, and then placing it in a tube furnace and calcining it in a hydrogen-argon mixed atmosphere (hydrogen mass ratio 5%) at a calcination temperature of 600°C and a heating rate of 8°C min -1 , the calcination time is 5h, and a high-activity and high-capacity electrode material is obtained.
[0072] Embodiment 12:
[0073] 1) Take 1g of zinc smelting anode mud, reduce its particle size by ball milling, and then disperse it in 10mL of leaching solution, the leaching solution is a mixed solution of hydrogen peroxide and sulfuric acid (acid concentration is 1.0molL -1 , H2O2 concentration is 0.1 molL -1 ), at 50°C, stirring was continued for 6h;
[0074] 2) The mixed solution was vacuum filtered to separate the leaching solution (the manganese leaching concentration was 5.2 g / L -1 , the zinc leaching concentration is 0.3gL -1 ), put 2.0molL -1 of sodium hydroxide solution and continued stirring; performing vacuum filtration to obtain a transition metal mixed gel residue;
[0075] 3) freeze-drying the transition metal mixed gel residue, grinding it, and then mixing it with thiourea at a mixing mass ratio of 1:3, and then placing it in a tube furnace and calcining it in a hydrogen-argon mixed atmosphere (hydrogen mass ratio 5%) at a calcination temperature of 600°C and a heating rate of 8°C min -1 , the calcination time is 5h, and a high-activity and high-capacity electrode material is obtained.
[0076] Embodiment 13:
[0077] 1) Take 1g of zinc smelting anode mud, reduce its particle size by ball milling, and then disperse it in 10mL of leaching solution, which is a mixed solution of hydrogen peroxide and sulfuric acid (acid concentration is 1.0 mol L -1 , H2O2 concentration is 0.1 mol L -1 ), at 50°C, stirring was continued for 6h;
[0078] 2) The mixed solution was vacuum filtered to separate the leaching solution (the manganese leaching concentration was 5.2 g / L -1 , the zinc leaching concentration is 0.3gL -1 ), put 1.0 mol L -1 of sodium hydroxide solution and continued stirring; performing vacuum filtration to obtain a transition metal mixed gel residue;
[0079] 3) The transition metal mixed gel residue was dried by blast drying, ground, and then mixed with thiourea at a mixing ratio of 1:3, and then placed in a tube furnace and calcined in a hydrogen-argon mixed atmosphere (hydrogen mass ratio 5%) at a calcination temperature of 600°C and a heating rate of 8°C min -1 , the calcination time is 5h, and a high-activity and high-capacity electrode material is obtained.
[0080] Embodiment 14:
[0081] 1) Take 1g of zinc smelting anode mud, reduce its particle size by ball milling, and then disperse it in 10mL of leaching solution, which is a mixed solution of hydrogen peroxide and sulfuric acid (acid concentration is 1.0 mol L -1 , H2O2 concentration is 0.1 molL -1 ), at 50°C, stirring was continued for 6h;
[0082] 2) The mixed solution was vacuum filtered to separate the leaching solution (the manganese leaching concentration was 5.2 g / L -1 , the zinc leaching concentration is 0.3gL -1 ), put 1.0molL -1 of sodium hydroxide solution and continued stirring; performing vacuum filtration to obtain a transition metal mixed gel residue;
[0083] 3) The transition metal mixed gel residue was freeze-dried, ground, and then mixed with sulfur powder at a mixing mass ratio of 1:3, and then placed in a tube furnace and calcined in a hydrogen-argon mixed atmosphere (hydrogen mass ratio 5%) at a calcination temperature of 600°C and a heating rate of 8°C min -1 , the calcination time is 5h, and a high-activity and high-capacity electrode material is obtained.
[0084] Embodiment 15:
[0085] 1) Take 1g of zinc smelting anode mud, reduce its particle size by ball milling, and then disperse it in 10mL of leaching solution, the leaching solution is a mixed solution of hydrogen peroxide and sulfuric acid (acid concentration is 1.0molL -1 , H2O2 concentration is 0.1 molL -1 ), at 50°C, stirring was continued for 6h;
[0086] 2) The mixed solution was vacuum filtered to separate the leaching solution (the leaching amount of manganese element was 5.2 g / L -1 , zinc element leaching solution concentration 0.3gL -1 ), put 1.0 mol L -1 of sodium hydroxide solution and continued stirring; performing vacuum filtration to obtain a transition metal mixed gel residue;
[0087] 3) freeze-drying the transition metal mixed gel residue, grinding it, and then mixing it with thiourea at a mixing mass ratio of 1:2, and then placing it in a tube furnace and calcining it in a hydrogen-argon mixed atmosphere (hydrogen mass ratio 5%) at a calcination temperature of 600°C and a heating rate of 8°C min -1 , the calcination time is 5h, and a high-activity and high-capacity electrode material is obtained.
[0088] Embodiment 16:
[0089] 1) Take 1g of zinc smelting anode mud, reduce its particle size by ball milling, and then disperse it in 10mL of leaching solution, which is a mixed solution of hydrogen peroxide and sulfuric acid (acid concentration 1.0 mol L -1 , H2O2 concentration is 0.1 molL -1 ), at 50°C, stirring was continued for 6h;
[0090] 2) The mixed solution was vacuum filtered to separate the leaching solution (the manganese leaching concentration was 5.2 g / L -1 , the zinc leaching concentration is 0.3gL -1 ), put 1.0 mol L -1 of sodium hydroxide solution and continued stirring; performing vacuum filtration to obtain a transition metal mixed gel residue;
[0091] 3) freeze-drying the transition metal mixed gel residue, grinding it, and then mixing it with thiourea at a mixing mass ratio of 1:10, and then placing it in a tube furnace and calcining it in a hydrogen-argon mixed atmosphere (hydrogen mass ratio 5%) at a calcination temperature of 600°C and a heating rate of 8°C min -1 , the calcination time is 5h, and a high-activity and high-capacity electrode material is obtained.
[0092] Embodiment 17:
[0093] 1) Take 1g of zinc smelting anode mud, reduce its particle size by ball milling, and then disperse it in 10mL of leaching solution, the leaching solution is a mixed solution of hydrogen peroxide and sulfuric acid (acid concentration is 1.0molL -1 , H2O2 concentration is 0.1 molL -1 ), at 50°C, stirring was continued for 6h;
[0094] 2) The mixed solution was vacuum filtered to separate the leaching solution (the manganese leaching concentration was 5.2 g / L -1 , the zinc leaching concentration is 0.3gL -1 ), put 1.0 mol L -1 of sodium hydroxide solution and continued stirring; performing vacuum filtration to obtain a transition metal mixed gel residue;
[0095] 3) The transition metal mixed gel residue was freeze-dried, ground, and then mixed with thiourea at a mixing mass ratio of 1:3, and then placed in a tubular furnace and calcined under a nitrogen atmosphere at a calcination temperature of 600°C and a heating rate of 8°C min -1 , the calcination time is 5h, and a high-activity and high-capacity electrode material is obtained.
[0096] Embodiment 18:
[0097] 1) Take 1g of zinc smelting anode mud, reduce its particle size by ball milling, and then disperse it in 10ml of leaching solution, which is a mixed solution of hydrogen peroxide and sulfuric acid (acid concentration is 1.0molL -1 , H2O2 concentration is 0.1 molL -1 ), at 50°C, stirring was continued for 6h;
[0098] 2) The mixed solution was vacuum filtered to separate the leaching solution (the manganese leaching concentration was 5.2 g / L -1 , the zinc leaching concentration is 0.3gL -1 ), put 1.0 mol L -1 of sodium hydroxide solution and continued stirring; performing vacuum filtration to obtain a transition metal mixed gel residue;
[0099] 3) freeze-drying the transition metal mixed gel residue, grinding it, and then mixing it with thiourea at a mixing mass ratio of 1:3, and then placing it in a tube furnace and calcining it in a hydrogen-argon mixed atmosphere (hydrogen mass ratio 5%) at a calcination temperature of 500°C and a heating rate of 8°C min -1 , the calcination time is 5h, and a high-activity and high-capacity electrode material is obtained.
[0100] Embodiment 19:
[0101] 1) Take 1g of zinc smelting anode mud, reduce its particle size by ball milling, and then disperse it in 10ml of leaching solution, which is a mixed solution of hydrogen peroxide and sulfuric acid (acid concentration is 1.0molL -1 , H2O2 concentration is 0.1 molL -1 ), at 50°C, stirring was continued for 6h;
[0102] 2) The mixed solution was vacuum filtered to separate the leaching solution (the manganese leaching concentration was 5.2 g / L -1 , the zinc leaching concentration is 0.3gL -1 ), put 1.0 mol L -1 of sodium hydroxide solution and continued stirring; performing vacuum filtration to obtain a transition metal mixed gel residue;
[0103] 3) freeze-drying the transition metal mixed gel residue, grinding it, and then mixing it with thiourea at a mixing mass ratio of 1:3, and then placing it in a tube furnace and calcining it in a hydrogen-argon mixed atmosphere (hydrogen mass ratio 5%) at a calcination temperature of 800°C and a heating rate of 8°C min -1 , the calcination time is 5h, and a high-activity and high-capacity electrode material is obtained.
[0104] Embodiment 20
[0105] 1. Sample:
[0106] In each of Examples 1 to 19, the zinc smelting anode mud is anode mud obtained from the market. Three materials, high-capacity and high-activity transition metal mixed sulfide, acetylene black, and sodium hydroxymethyl cellulose (CMC), are added with a certain amount of deionized water in a mass ratio of 8 / 1 / 1 to prepare a uniform slurry. The obtained slurry is coated on a copper foil, and then placed in a vacuum oven at 100° C. for 12 hours for drying. The obtained pole piece is cut by a slicer into small discs with a diameter of 0.7 cm to 1.0 cm, which become the obtained negative electrode material, wherein the copper foil surface is loaded with more than 1.0 to 2.0 mg of active substance.
[0107] The obtained negative electrode sheet, electrolyte, lithium sheet, battery shell, diaphragm, etc. are placed in an argon glove box for battery assembly. After sealing, the obtained battery is an assembled button battery.
[0108] Note: All examples adopt the above-mentioned electrode material preparation method.
[0109] 2. Experimental methods
[0110] The button cell was left to stand for 12 h and then placed on a blue electric test channel for electrochemical performance testing, where the current density was set to 0.50A. -1 , the voltage range is set to 0.01V~3.0V and the test cycle is 100 cycles. The data obtained is the data directly displayed on the blue electricity tester, which can be directly used.
[0111] 3. Test results: see Table 1
[0112] Table 1: Experimental conditions and test results in each embodiment
[0113]
[0114]
Claims
1. A method for preparing high-capacity electrode materials based on zinc smelting anode mud, characterized in that: The zinc smelting anode mud is leached by a wet method to obtain a mixed transition metal ion solution; the mixed transition metal ion solution is hydrolyzed and precipitated to obtain a transition metal mixed gel; the transition metal mixed gel is sulfided and roasted to obtain an electrode material; the wet leaching adopts at least one of an acid solution containing ferrous ions, an acid solution containing hydrogen peroxide or an acid solution containing sulfite as a leaching agent.
2. The method for preparing high-capacity electrode materials based on zinc smelting anode mud according to claim 1, characterized in that: The concentration of ferrous ions in the acid solution containing ferrous ions is 0.05-0.5 mol L -1 The acid concentration is 0.5~2 mol L -1 ; The concentration of hydrogen peroxide in the acid solution containing hydrogen peroxide is 0.05-0.5 mol L -1 , the acid concentration is 0.5~2 molL -1 ; The concentration of sulfite in the sulfite-containing acid solution is 0.05-0.5 mol L -1 The acid concentration is 0.5~2 mol L -1 .
3. A method for preparing high-capacity electrode materials based on zinc smelting anode mud according to claim 1 or 2, characterized in that: The conditions of the wet leaching are: liquid-solid ratio of 1 mL: 1 g to 100 mL: 1 g, leaching temperature of 30° C. to 100° C., and leaching time of 0.5 h to 12 h.
4. The method for preparing high-capacity electrode materials based on zinc smelting anode mud according to claim 1, characterized in that: The hydrolysis precipitate was prepared at a concentration of 0.1 mol L -1 ~ 2.0 mol L -1 An alkaline solution is used as a precipitant; The alkaline solution includes at least one of sodium hydroxide solution, lithium hydroxide solution, potassium hydroxide solution and ammonia water.
5. The method for preparing high-capacity electrode materials based on zinc smelting anode mud according to claim 1, characterized in that: In the process of the sulfurization roasting, thiourea and / or sulfur powder are used as the vulcanizing agent; The mass of the vulcanizing agent is 2 to 10 times the mass of the transition metal mixed gel.
6. The method for preparing high-capacity electrode material based on zinc smelting anode mud according to claim 1 or 5, characterized in that: The calcination conditions are: in a protective atmosphere, at 5-15°C min -1 The heating rate is increased to 500~800℃ and calcined for 4h~10h.
7. A high capacity electrode material, characterized in that: Obtained by the preparation method according to any one of claims 1 to 6.
8. The use of a high-capacity electrode material according to claim 7, characterized in that: Used as negative electrode material in lithium-ion batteries.